2000
DOI: 10.1136/bmj.320.7240.967
|View full text |Cite
|
Sign up to set email alerts
|

Association between postnatal catch-up growth and obesity in childhood: prospective cohort study

Abstract: Objective To identify predictors of postnatal catch-up growth from birth to two years and its relation to size and obesity at five years. Design Regional prospective cohort study. Setting Avon longitudinal study of pregnancy and childhood, United Kingdom. Subjects 848 full term singletons from a 10% random sample of the Avon longitudinal study of pregnancy and childhood. Main outcome measures Maternal birth weight, prepregnancy weight, pregnancy weight gain, height, smoking, and parity, and paternal height. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

72
1,224
11
62

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,474 publications
(1,369 citation statements)
references
References 19 publications
72
1,224
11
62
Order By: Relevance
“…40 Furthermore, bioactive factors in breast milk might modulate growth factors, which inhibit adipocyte differentiation in vitro. 41,42 Finally, it has been suggested that exclusively breastfed infants adapt more readily to new foods such as fruits and vegetables, thus influencing the subsequent caloric density of their diet. 43 Considering its many benefits to mother, child and society, exclusive breastfeeding is the recommended practice of infant feeding for the first 6 months of life, 44 and ongoing efforts to support breastfeeding should continue regardless of whether it is an important factor protecting against childhood overweight.…”
Section: Discussionmentioning
confidence: 99%
“…40 Furthermore, bioactive factors in breast milk might modulate growth factors, which inhibit adipocyte differentiation in vitro. 41,42 Finally, it has been suggested that exclusively breastfed infants adapt more readily to new foods such as fruits and vegetables, thus influencing the subsequent caloric density of their diet. 43 Considering its many benefits to mother, child and society, exclusive breastfeeding is the recommended practice of infant feeding for the first 6 months of life, 44 and ongoing efforts to support breastfeeding should continue regardless of whether it is an important factor protecting against childhood overweight.…”
Section: Discussionmentioning
confidence: 99%
“…Size at 3 months is therefore more highly related to genotype than size at birth and is a better predictor of adult stature. In humans, there is evidence that catch-up growth is associated with an increased risk of insulin resistance as an adult (Ong et al, 2000).…”
Section: Prenatal Programmingmentioning
confidence: 99%
“…One probable cause of the inconsistency between studies is that birth weight acts as a marker not only of growth during fetal life but also of postnatal growth. 54 Small babies tend to catch-up during infancy, 55 and it is variability in infant growth that has been associated most reliably with variability in adiposity in childhood and beyond. However, even here, the findings differ between Western and developing countries.…”
Section: Intra-human Variability In Thriftmentioning
confidence: 99%